Extracellular Vesicles as a Potential Biomarker of Pulmonary Arterial Hypertension in Systemic Sclerosis - Stelvio Tonello; Davide D’Onghia; Annalisa Di Ruscio; Silvia Maria Mora; Federica Vincenzi; Giulia Caria; Alessia Fracchia; Nicole Vercellino; Benedetta Bussolati; Adele Tanzi; Manuela Rizzi; Rosalba Minisini; et al. (Pharmaceuticals)
Introduction: Pulmonary arterial hypertension (PAH) and interstitial lung disease (ILD) are severe complications of patients with systemic sclerosis (SSc). Currently, there are a few tests for early identification of these conditions, although they are invasive and time-consuming. Extracellular vesicles (EVs) offer a promising possibility for gathering information on tissue health. This study aims to characterize EVs in cases of systemic sclerosis complicated by pulmonary hypertension and pulmonary fibrosis. Methods: A cohort of 58 patients with SSc was evaluated, including 14 with pulmonary hypertension, 17 with pulmonary fibrosis, and 27 without complications. Additionally, 11 healthy subjects, matched for sex and age, served as a control group. EVs were characterized by using a MACSplex kit to analyze the expression of 37 membrane markers. Results: After the overall analysis, we show that EVs from SSc patients had higher expression of CD146, CD42a, and CD29 (p = 0.03, p = 0.02 and p = 0.05) but lower expression of HLA-ABC with respect to the control patients (p = 0.02). Multivariate analyses demonstrated that only CD42a has a significant association with the disease (p = 0.0478). In group comparative analyses (PAH, ILD, uncomplicated systemic sclerosis (named SSc no PAH no ILD), and controls), CD3 and CD56 were higher in PAH patients, with respect to the controls, ILD, and the group SSc no PAH no ILD (CD3: p = 0.01, p = 0.003, p = 0.0005; CD56: p = 0.002, p < 0.0001, p = 0.0002). HLA-DR showed higher expression in PAH patients with respect to ILD patients (p = 0.02), CD25 showed higher expression in PAH patients with respect uncomplicated SSc (p = 0.02), and CD42a showed higher expression in PAH patients with respect to the controls (p = 0.03); nevertheless, multivariate analyses demonstrated that only CD3 retained its association with PAH. Conclusions: The expression of CD42a, a platelet-derived marker indicating endothelial damage, suggests its potential to provide information on the state of the microcirculation in systemic sclerosis. The higher expression of CD3 on the surface of the EVs in PAH patients might indicate increased T-cell activity in tissues, with a possible association with the development of pulmonary hypertension.